Machine Learning Based Diagnostic Paradigm in Viral and Non-Viral Hepatocellular Carcinoma - Arun Asif; Faheem Ahmed; Zeeshan; Javed Ali Khan; Eman Allogmani; Nora El Rashidy; Sobia Manzoor; Muhammad Shahid Anwar (IEEE Access, 2024)
Viral and non-viral hepatocellular carcinoma (HCC) is becoming predominant in developing countries. A major issue linked to HCC-related mortality rate is the late diagnosis of cancer development. Although traditional approaches to diagnosing HCC have become gold-standard, there remain several limitations due to which the confirmation of cancer progression takes a longer period. The recent emergence of artificial intelligence tools with the capacity to analyze biomedical datasets is assisting traditional diagnostic approaches for early diagnosis with certainty. Here we present a review of traditional HCC diagnostic approaches versus the use of artificial intelligence (Machine Learning and Deep Learning) for HCC diagnosis. The overview of the cancer-related databases along with the use of AI in histopathology, radiology, biomarker, and electronic health records (EHRs) based HCC diagnosis is given.